Planning Of Wastewater Treatment Plant (WWTP) Analysis: (Case Study in Condominium Pasir Putih View Hotel - Situbondo) - Putri Ermadani; F Rooslan Edy Santosa (Journal of World Conference (JWC), 2020)
Increasing population and household growth cause the need for housing to shift to urban areas and develop into multi-story housing such as condominiums, apartments and so on as a result of urbanization. Pasir Putih View Condominium Hotel - Situbondo (Condotel) is one of the real indicators of the economic, social and cultural progress of the people in a region. The construction of the Condominium Hotel (Condotel) project requires careful planning in terms of structure, architecture, and also mechanical electrical plumbing. Building planning, especially on mechanical electrical plumbing (MEP) must be adjusted to the number of guests or people who are in the condotel area. One of them is planning the Waste Water Treatment Plant (WWTP) which will be recycled and used for one of the condotel requirements. This WWTP plan starts with determining the total clean water requirements and the total flushing needs needed. The method of data analysis is done by calculating the total water discharge planning needed and the results from the dimensions of the WWTP space needed. The results obtained are in the form of the calculated discharge volume and WWTP space data which is accompanied by shop drawing images in which a comparison of the old design with the new WWTP design. The discharge volume of the total clean water requirement obtained from the calculation is 179.04 m3. The calculation for the dimensions of the WWTP space needed is 13.5mx5mx4m. From the type of WWTP, the time to treat wastewater into environmentally-friendly (non-consumption) water can be 50% faster. WWTP type planning is done to produce more efficient planning of the WWTP that had been planned by the previous consultant while not ignoring security factors